2002
DOI: 10.1152/ajplung.2002.282.1.l155
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide exposure: effects on airway and blood cells

Abstract: This study examined the effects of nitrogen dioxide (NO(2)) exposure on airway inflammation, blood cells, and antiviral respiratory defense. Twenty-one healthy volunteers were exposed on separate occasions to air and 0.6 and 1.5 ppm NO(2) for 3 h with intermittent moderate exercise. Phlebotomy and bronchoscopy were performed 3.5 h after each exposure, and recovered cells were challenged with respiratory viruses in vitro. Blood studies revealed a 4.1% NO(2) dose-related decrease in hematocrit (P = 0.003). Circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 40 publications
7
55
1
Order By: Relevance
“…Frampton et al (35) found an inflammatory response that persisted at least 18 h after exposure, while Blomberg et al (36) demonstrated major decrements in FEV 1 just after exposure and this lung function indicator response was attenuated after repeated exposures, even in the presence of a persistent neutrophilic inflammation in the airways. They concluded that NO 2 is a proinflammatory air pollutant under conditions of repeated exposure.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Frampton et al (35) found an inflammatory response that persisted at least 18 h after exposure, while Blomberg et al (36) demonstrated major decrements in FEV 1 just after exposure and this lung function indicator response was attenuated after repeated exposures, even in the presence of a persistent neutrophilic inflammation in the airways. They concluded that NO 2 is a proinflammatory air pollutant under conditions of repeated exposure.…”
Section: Modelmentioning
confidence: 99%
“…Experimental studies on healthy nonsmoking subjects have shown that adverse inflammatory effects on the airways may occur due to acute exposure to NO 2 (2 ppm) and can be determined by bronchoalveolar lavage (35) and FEV 1 measurements (36). Frampton et al (35) found an inflammatory response that persisted at least 18 h after exposure, while Blomberg et al (36) demonstrated major decrements in FEV 1 just after exposure and this lung function indicator response was attenuated after repeated exposures, even in the presence of a persistent neutrophilic inflammation in the airways.…”
Section: Modelmentioning
confidence: 99%
“…However, the mechanism of NO 2 toxicity on the airway is quite complex, and the toxicity varies depending on the dose, length, and the way of exposure. A meta-analysis of epidemiological studies for NO 2 effects reported that a 16-ppb increase in NO 2 level was associated with a 20% increase in the odds ratio of respiratory illness, whereas a clinical study indicates that a biologically effective dose of NO 2 was 600 ppb (Hasselblad et al 1992;Frampton et al 2002). NO 2 can reach the lower respiratory tract in the lung due to its limited solubility (Frampton et al 2002;Muller et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of epidemiological studies for NO 2 effects reported that a 16-ppb increase in NO 2 level was associated with a 20% increase in the odds ratio of respiratory illness, whereas a clinical study indicates that a biologically effective dose of NO 2 was 600 ppb (Hasselblad et al 1992;Frampton et al 2002). NO 2 can reach the lower respiratory tract in the lung due to its limited solubility (Frampton et al 2002;Muller et al 1998). Then, NO 2 could interact with the respiratory epithelial cell surface and produce reactive oxygen and nitrogen species (Persinger et al 2001;Frampton et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation